At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
you just do
3x=x+4
subtract x from both sides
2x=4
divide 2 from both sides
x=2
y=2+4
y=6
(x,y)= (2,6)
3x=x+4
subtract x from both sides
2x=4
divide 2 from both sides
x=2
y=2+4
y=6
(x,y)= (2,6)
y = x + 4
y = 3x
3x = x + 4
- x - x
2x = 4
2 2
x = 2
y = x + 4
y = 2 + 4
y = 6
(x, y) = (2, 6)
y = 3x
3x = x + 4
- x - x
2x = 4
2 2
x = 2
y = x + 4
y = 2 + 4
y = 6
(x, y) = (2, 6)
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.